2021
DOI: 10.3389/fcvm.2021.665303
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Stent Healing in Cancer Patients—An Optical Coherence Tomography Perspective

Abstract: Objective: This study assessed stent healing patterns and cardiovascular outcomes by optical coherence tomography (OCT) in cancer patients after drug-eluting stent (DES) placement.Background: Cancer treatment, owing to its cytotoxic and antiproliferative effects, could delay stent healing and increase stent thrombosis risk, especially when dual antiplatelet therapy (DAPT) is discontinued early for oncological treatment. OCT can assess stent endothelialization and other healing parameters, which may provide cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…By utilizing this technology, it has been able to obtain important measurements of stenotic lesions, minimal luminal area (MLA), and characteristics of atherosclerotic plaques, but also calcification and thrombus formation in cancer patients with coronary artery disease and may guide more appropriate therapeutic management. After percutaneous coronary interventions, further data acquisitions on stent apposition and follow-up studies of in-stent restenosis add important improvements to advanced coronary interventions since lesions of coronary patients may be complex and advanced interventional techniques may be used for therapeutic management (rotablation techniques, shock wave balloons, intravascular lithotripsy) [ 35 ]. OCT may be additionally a very useful imaging modality for treatment decisions on dual antiplatelet therapy discontinuation after percutaneous coronary interventions [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…By utilizing this technology, it has been able to obtain important measurements of stenotic lesions, minimal luminal area (MLA), and characteristics of atherosclerotic plaques, but also calcification and thrombus formation in cancer patients with coronary artery disease and may guide more appropriate therapeutic management. After percutaneous coronary interventions, further data acquisitions on stent apposition and follow-up studies of in-stent restenosis add important improvements to advanced coronary interventions since lesions of coronary patients may be complex and advanced interventional techniques may be used for therapeutic management (rotablation techniques, shock wave balloons, intravascular lithotripsy) [ 35 ]. OCT may be additionally a very useful imaging modality for treatment decisions on dual antiplatelet therapy discontinuation after percutaneous coronary interventions [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A study using OCT to evaluate stent healing after DES placement showed adequate stent healing in cancer patients despite a shorter course of DAPT (< 6 months) in 61% of them. Findings were matched with stent healing value for DES in non-cancer patients ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…A single-center prospective study in cancer patients with a recently placed DES (within 1–12 months), who needed early discontinuation of their DAPT, showed that optical coherence tomography (OCT) imaging can be used to identify those at low risk for discontinuation and can thus proceed with their cancer-related surgery or procedures [ 86 ]. A similar study using OCT to evaluate stent healing after DES placement showed adequate stent healing in cancer patients, despite a short course of DAPT (< 6 months) in over 61% of patients [ 87 ].…”
Section: Approach To Coronary Artery Disease Diagnosis and Managementmentioning
confidence: 99%